Основи саморозвитку економіки держави - Яковенко, Р. В.; Yakovenko, R. (Кропивницький : сайт tusovka.kr.ua, 2018)
Стаття розкриває аспекти саморозвитку економіки через питання еволюції, ядер саморозвитку та суперечностей технологічних, соціальних та соціально-економічних укладів. The article reveals the aspects of self-development of the economy through issues of evolution, the nuclei of self-development and the contradictions of technological, social and socio-economic patterns.
Basics of self-development of the state economy
Keywords: еволюція; ентропія; саморозвиток; біфуркація; економічна генетика; технологічний уклад; evolution; entropy; self-development; bifurcation; economic genetics; technological approach